ESENSI ZIHAR MENURUT HUKUM ISLAM : (Studi Pemikiran Imam Abu Hanifah dan Imam Malik) - adrianto; Khalid Sitorus (EL-ADABI : Jurnal Studi Islam, 2024)
Zihar caused controversy between Imam Abu Hanifah and Imam Malik regarding the husband's statement that mentions body parts other than the back or mentions women other than mothers who are forbidden to marry forever. This research uses a qualitative approach with a literature study method. The results show that according to Imam Abu Hanifah, zihar only occurs if the husband mentions body parts that are forbidden to be seen. In contrast, Imam Malik argues that the mention is already included in the category of zihar. In terms of divorce law, Imam Abu Hanifah argues that zihar is not the same as talaq (divorce), while Imam Malik argues that zihar is close to talaq. Imam Abu Hanifah was of the opinion that zihar is close to talaq. Lastly, Imam Abu Hanifah was of the opinion that to erase zihar, one only needs to return to the teachings of Islam, while Imam Malik was of the opinion that the zihar offender must pay kifarat as a form of atonement.